(untitled) (American Journal of Islam and Society, 2014)
In his most recent work, The Coup: 1953, the CIA, and the Roots of Modern U. S.-Iranian Relations, Ervand Abrahamian (Distinguished Professor of Iranian and Middle Eastern History, Baruch College of the City University, New York) recounts a definitive moment of modern Iranian history that overshadows Iranian-American relations to this day. Drawing on a remarkable variety of sources – accessible Iranian official documents, the Foreign Office and State Department files, memoirs and biographies, newspaper articles published during the crisis, recent Persian-language books published in Iran, a CIA report leaked in 2000 known as “the Wilber document,” and two contemporary oral history projects (the Iranian Oral History Project at Harvard University and the Iranian Left history project in Berlin) – the author provides a detailed and thorough account of the 1953 coup. Challenging the dominant consensus among academicians and political analysts that the coup transpired because of the Cold War rivalries between the West and the Soviet Union, he locates it within the paradigms of the clash between an old imperialism and a burgeoning nationalism. He then traces its origins to Iran’s struggle to nationalize its oil industry and the Anglo-American alliance against this effort. The book is divided into four chapters. The first chapter, “Oil Nationalization,” narrates the history of Iran’s oil industry and various encounters between the Anglo-Iranian Oil Company (AIOC) and the Iranians. The Anglo- Persian Oil Company (APOC), an English company founded in 1908 following the discovery of a large oil field in Masjed Soleiman in southern Iran, was renamed AIOC in 1935. AIOC gradually turned into a vital British asset and provided its treasury with more than £24 million a year in taxes and £92 million in foreign exchange in the first decades of the twentieth century ...